Residential use of solar water heating in Turkey: A novel thermo-economic optimization for energy savings, cost benefit and ecology. (10th December 2018) - Yılmaz, İbrahim Halil
Abstract: Recent trends in residential solar water heating and its efficient usage in Turkey were presented in this study. A novel methodology for determining the optimum orientation and sizing of water-in-glass evacuated tube solar water heating systems has been outlined. Transient modeling was conducted for the prediction of a full year's system performance via the System Advisor Model. In this model, the typical meteorological year data of certain climate zones in Turkey were considered, daily hot water consumption was estimated using the Rand hot water profile, and the monthly averaged mains water temperatures measured by the municipalities were analyzed. In addition, a typical performance rating of a water-in-glass evacuated tube collector produced by the collector manufacturer in Turkey was taken into consideration, and the effects of collector area, storage tank volume, daily average delivery temperature and daily hot water consumption data on the annual solar fraction were analyzed. The verification of the simulation results were compared with the literature and good agreement was obtained. Subsequently, a thermo-economic optimization was employed by using P 1 ‒ P 2 methodology. The methodology presented guarantees to obtain reliable results with a minimal run-time. The diminution in the initial system cost and payback period are shown to be possibly achieved at the level of 7.5% in a 1.5 year period, respectively, while the energy savings are approximately 12% higher annually when implementing optimum results. The results indicate that Turkey would save 300 MWth annually if evacuated tube solar water heaters in Turkey's cities are configured based on optimal sizing. An evacuated solar water heater in a typical residential building in Turkey has the potential to mitigate 5–22 g CO2 -equivalent/kWh of greenhouse gas emissions per annum if properly installed. Graphical abstract: Highlights: A methodology for optimizing of water-in-glass collector systems was presented. A transient modeling was conducted using the System Advisor Model simulation tool. Verification of the simulation was compared with the literature in good agreement. A thermo-economic optimization was employed with a minimal run-time. Optimum collector design was proposed for promoting energy, economy and ecology.